Tax incentives as a stimulating mechanism for creative industries in regional economy - Karpova O. M.; Turgel I. D. (Вестник Пермского университета: Серия Экономика)
Introduction. The article refers to international practices and proposes tax incentives as a stimulating mechanism for creative industries in Russia. The development of creative industries is a crucial aspect of both economic and cultural growth. However, tax support measures in Russia remain underdeveloped and inconsistent across regions.